Analysis of Factors Affecting the Unbalanced Development of Sports in Zhaoqing city - Xiang, Jun; You, Guibing (International Journal of Social Sciences and Public Administration, 2024)
This study utilizes the factor analysis method, draws on theoretical knowledge in the field of economics about the measurement of unbalanced development, and takes each region of Zhaoqing City as an individual unit, and measures and studies the evaluation indexes of unbalanced development of sports in each region and its influencing factors on the basis of comparing each region, with a view to providing a reference basis for the balanced development of sports in Zhaoqing City. The results show that (1) economic factors, socio-cultural factors, policy factors, geographic and natural factors, technological and information factors, and demographic factors are the primary factors affecting the unbalanced development of sports in Zhaoqing City at the first level, and that differences in the level of economic development, the development of the sports industry, the concept of sports, educational resources, sports policies, infrastructure development, topography, climatic factors, mobile population, digital sports facilities, and information dissemination are the secondary factors affecting the unbalanced development of sports in Zhaoqing; (2) proposed paths for the balanced development of sports in Zhaoqing, such as sports facilities planning, diversification of sports programs, sports talent cultivation, social sports organization and promotion, the application of digital technology, policy support and financial investment.